The Anatomy of Courage - Moran, John (London Constable, 1946)
'I set out to find how courage is born and how it is sustained in a modern army of a free people. The soldier is alone in his war with terror and we have to recognise the first signs of his defeat, that we may come in time to his rescue.' Lord MoranFirst published in 1945 this early, groundbreaking account of the psychological effects of war, recounted by means of vivid first-hand observation and anecdote, came at a time when shell-shock was equated with lack of moral fibre. In 1940, Moran became Churchill's doctor and his position as a one of history's most important war physicians was s.
Keywords: Courage -- Fear -- Psychology, Military